Armadilha Óptica de Dipolo para 88Sr - Magnani, Pedro Henrique Nantes (Universidade Federal de São Carlos, 2019)
In this work, we present the study of light and matter interaction through the building and operation of a cold atoms experiment. The motivation is to study light scattering in the dense regime, where this phenomenon becomes a collective effect, since the distance between atoms is such that inter-atomics effects must be considerated (in terms of density, one could say that the sample belongs to the dense regime when its density is of the order of 1/A3, where A is the wavelenght) and also because scientific comunity hasn’t fully understand it yet. To achieve such a regime, we use the luminous force that happens when an atom interacts with a laser beam. First we use the radiation pressure force to create a magneto-optical trap, and then use the dipolar force to create the final objective of this dissertation: the optical dipole trap. In the end, we have achieved an ODT sample with 0,17 density in 1/A3 unitys. Such density does not characterize the sample as a dense one, but the problems of such results are already being solved, making a dense sample perfectly accessible, which we can say it’s a very good result for our first optica dipole trap ever. Now, the experiment is at the door of a far over interesting physics, which is the study of collective scattering of light.
Optical Dipole Trap for 88Sr
Keywords: Dipolo; Armadilha óptica; ODT; MOT; Dipole; CIENCIAS EXATAS E DA TERRA::FISICA